Complete response to anti-PD-1 nivolumab in massive skin metastasis from melanoma: efficacy and tolerability in an elderly patient. Issue 7 (August 2017) - Sponghini, Andrea; Patrucco, Federica; Giorgione, Roberto; Farinelli, Pamela; Zottarelli, Francesca; Rondonotti, David; Savoia, Paola
Abstract : The advent of immune checkpoint inhibitors anti-PD-1/PD-L1 has delivered new and effective treatment options with proven clinical benefits for patients affected by metastatic melanoma. The 30–40% of treated patients experience an objective tumour regression, with a significantly prolonged survival and an improved quality of life. Here, we report a case of a 75-year-old Caucasian woman affected by a massive cutaneous metastasis from a BRAF wild-type melanoma who experienced multiple relapses after surgery and repeated electrochemotherapy treatments. A poor response was observed after systemic therapy with ipilimumab, whereas a marked reduction in the lesion size was obtained during the treatment with nivolumab, with an objectively complete response after 6 months. Therapy was well tolerated, without immune-related side effects. During treatment, LDH levels decreased up to the standard values. Our experience confirms the good efficacy and the safety of anti-PD-1 nivolumab for the treatment of relapsed or refractory massive skin lesions, also in elderly patients.